A Systematic Review of the Uptake and Adherence Rates to Supervised Exercise Programs in Patients with Intermittent Claudication - Harwood, Amy-Elizabeth; Smith, George E.; Cayton, Thomas; Broadbent, Edward; Chetter, Ian C. (Annals of vascular surgery, 2016)
Intermittent claudication (IC) is a common and debilitating symptom of peripheral arterial disease and is associated with a significant reduction in a sufferer's quality of life. Guidelines recommend a supervised exercise program (SEP) as the primary treatment option; however, anecdotally there is a low participation rate for exercise in this group of patients. We undertook a systematic review of the uptake and adherence rates to SEPs for individuals with IC. The MEDLINE, Embase, and PubMed databases were searched up to January 2015 for terms related to supervised exercise in peripheral arterial disease. The review had 3 aims: first, to establish the rates of uptake to SEPs, second, the rates of adherence to programs, and finally to determine the reasons reported for poor uptake and adherence. Separate inclusion and/or exclusion criteria were applied in selecting reports for each aim of the review. Only 23 of the 53 potentially eligible articles for uptake analysis identified on literature searches reported any details of screened patients (n = 7,517) with only 24.2% of patients subsequently recruited to SEPs. Forty-five percent of screen failures had no reason for exclusion reported. Sixty-seven articles with 4,012 patients were included for analysis of SEP adherence. Overall, 75.1% of patients reportedly completed an SEP; however, only one article defined a minimal attendance required for SEP completion. Overall, 54.1% of incomplete adherence was due to patient withdrawal and no reason for incomplete adherence was reported for 16% of cases. Reporting of SEP trials was poor with regard to the numbers of subjects screened and reasons for exclusions. Only approximately 1 in 3 screened IC patients was suitable for and willing to undertake SEP. Levels of adherence to SEPs and definitions of satisfactory adherence were also lacking in most the current literature. Current clinical guidelines based on this evidence base may not be applicable to most IC patients and changes to SEPs may be needed to encourage and/or retain participants.